Negative Regulation of the Mis17-Mis6 Centromere Complex by mRNA Decay Pathway and EKC/KEOPS Complex in Schizosaccharomyces pombe. Issue 6 (1st June 2019) - Xu, Xingya; Nakazawa, Norihiko; Wang, Li; Arakawa, Orie; Yanagida, Mitsuhiro
Abstract: The mitotic kinetochore forms at the centromere for proper chromosome segregation. Deposition of the centromere-specific histone H3 variant, spCENP-A/Cnp1, is vital for the formation of centromere-specific chromatin and the Mis17-Mis6 complex of the fission yeast Schizosaccharomyces pombe is required for this deposition. Here we identified extragenic suppressors for a Mis17-Mis6 complex temperature-sensitive (ts) mutant, mis17-S353P, using whole-genome sequencing. The large and small daughter nuclei phenotype observed in mis17-S353P was greatly rescued by these suppressors. Suppressor mutations in two ribonuclease genes involved in the mRNA decay pathway, exo2 and pan2, may affect Mis17 protein level, as mis17 mutant protein level was recovered in mis17-S353P exo2 double mutant cells. Suppressor mutations in EKC/KEOPS complex genes may not regulate Mis17 protein level, but restored centromeric localization of spCENP-A/Cnp1, Mis6 and Mis15 in mis17-S353P . Therefore, the EKC/KEOPS complex may inhibit Mis17-Mis6 complex formation or centromeric localization. Mutational analysis in protein structure indicated that suppressor mutations in the EKC/KEOPS complex may interfere with its kinase activity or complex formation. Our results suggest that the mRNA decay pathway and the EKC/KEOPS complex negatively regulate Mis17-Mis6 complex-mediated centromere formation by distinct and unexpected mechanisms.